Pengaruh Pemberian Hormon Sitokinin Terhadap Pertumbuhan Okulasi Hijau Dan Okulasi Coklat Stum Mata Tidur Tanaman Karet (Hevea brasilliensis) KLON IRR 112 - Yosi Amnurrahman; Adrinal Adrinal; Irfan Suliansyah (Program Studi Agroteknologi Fakultas Pertanian Universitas Andalas, 2018)
The reseach was conducted in the Kebun Pembibitan Kelompok Tani Budidaya, Sungai Dareh, Dharmasraya fromJuly to October 2016. The aim of the study was to investigate the interaction between grafting and concentration ofbenzylaminopurine, to measure the growth of grafts treated with benzylaminopurine and to determine the bestconcentration of benzylaminopurine. A completely randomized factorial design was used. The first factor was thetype of bud (green or brown) and the second factor was benzylaminopurine concentration (0, 5, 10, 15, and 20ppm). The best concentration of benzylaminopurine for green buds was 10 ppm whereas the best concetration was20 ppm for brown buds.